Enterprise characteristics and external influencing factors of sustainable innovation: Based on China's innovation survey. (20th October 2022) - Wei, Jie; Li, Yong; Liu, Xuzhi; Du, Ying
Abstract: This paper discusses the main driving forces that influence the sustainable innovation of enterprises based on a three-dimensional framework at the organization level, individual level and system level. Using data from China's Innovation Survey, which is in line with the Community Innovation Survey（CIS）, this paper examines the behaviours and strategies of Chinese enterprises' sustainable innovation. The study finds that China's sustainable and innovative enterprises are generally large-scale, are long lasting, have good profitability and invest more in R&D and environmental protection. And the sustainable innovation of state-owned enterprises is significantly more than other enterprises. The primary purpose of enterprises engaged in sustainable innovation is to reduce environmental damage, but financial constraints are still an important obstacle for enterprises to overcome to carry out sustainable innovation. In addition, enterprises with more conservative senior executives and more political connections to government do not prefer sustainable innovation. The institutional pressure exerted by external environmental regulations and the cost constraints alleviated by government environmental protection subsidies are the key factors affecting enterprises' sustainable innovation. In conclusion, depicting the real situation of Chinese enterprises' sustainable innovation behaviour based on the survey framework and data of systematically identifying enterprises' innovation behaviour is beneficial to provide examples for developing countries related to sustainable innovation research.